A New Extended Exponentiated Exponential Distribution with Application to Truncated Life Tests - Braimah, Joseph; Ibrahim, Sule; Umar, Salisu Shehu; Bukoye , Abdulwasiu; Edike, Nnamdi (Journal of Statistical Modeling and Analytics (JOSMA), 2023)
In this paper, the Extended Exponentiated Exponential distribution was developed from the New Extended Exponentiated-G family of distributions. Some mathematical properties of the newly derived distribution such as moment, moment generating function, quantile function, hazard function, survival function, odd function, distribution of order statistic and maximum likelihood estimation were all derived. An acceptance sampling plan based on truncated life tests was also developed for the distribution. The minimum size, operating characteristic function values and minimum ratio of the sampling plan required to confirm the specified mean life are also presented. Real-life example was used to illustrate the results. A comparison study with different sampling plans and distributions by earlier authors is also carried out to demonstrate the advantage of the new plan over existing plans. The findings revealed that the proposed plan is better and can be conveniently useful by researchers and Quality Control Personnel in product acceptance sampling inspection.